Potensi Small Business dalam Meningkatkan Perekonomian Masyarakat: Studi Kasus UMKM Rumah Makan Minang Jl. Prof. H. M. Yamin Kota Medan - Santa Oktavia Turnip; Trizthan Irfan Hermawan; Arif Pratama Putra Nst; Salsabila Mawaddah Damanik; Dionisius Sihombing; Fadli Agus Triansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving economic growth at the local level and enhancing community welfare. This study aims to examine the potential of small businesses in strengthening the local economy through a case study of the Minang Restaurant MSME located on Jl. Prof. H. M. Yamin in Medan City. The research employs a qualitative descriptive method with a case study approach, involving field observations, in-depth interviews, and document analysis to obtain comprehensive data. The findings indicate that the presence of this MSME makes a significant contribution to job creation, stimulates local economic circulation, fosters entrepreneurial creativity, and expands community access to traditional culinary products. Moreover, the business demonstrates resilience in facing market competition by emphasizing high-quality products and excellent customer service. The study also highlights that the MSME’s ability to adapt to changing consumer preferences and utilize local resources strengthens its sustainability and competitiveness.Overall, small businesses, particularly culinary MSMEs, have substantial potential to enhance the local economy by empowering the workforce, increasing household incomes, promoting entrepreneurship, and preserving cultural heritage. The findings suggest that supporting and developing MSMEs can serve as an effective strategy for fostering inclusive economic growth and enhancing social and cultural vitality within local communities.